2021
DOI: 10.48550/arxiv.2102.08100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chickenpox Cases in Hungary: a Benchmark Dataset for Spatiotemporal Signal Processing with Graph Neural Networks

Abstract: Recurrent graph convolutional neural networks are highly effective machine learning techniques for spatiotemporal signal processing. Newly proposed graph neural network architectures are repetitively evaluated on standard tasks such as traffic or weather forecasting. In this paper, we propose the Chickenpox Cases in Hungary dataset as a new dataset for comparing graph neural network architectures. Our time series analysis and forecasting experiments demonstrate that the Chickenpox Cases in Hungary dataset is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…We evaluated our methods on a data set of chickenpox cases in Hungary (Rozemberczki et al, 2021b We observed similar results to the COVID-19 case: GP approaches outperformed the GNN approach, SHEK has shown comparable performance with separable kernel on the extrapolation task with more stable performance across the validation rounds. The separable kernel has shown better performance on the interpolation task than SHEK (DM-test, p = 0.05).…”
Section: Hungary Chickenpox Data Setmentioning
confidence: 69%
“…We evaluated our methods on a data set of chickenpox cases in Hungary (Rozemberczki et al, 2021b We observed similar results to the COVID-19 case: GP approaches outperformed the GNN approach, SHEK has shown comparable performance with separable kernel on the extrapolation task with more stable performance across the validation rounds. The separable kernel has shown better performance on the interpolation task than SHEK (DM-test, p = 0.05).…”
Section: Hungary Chickenpox Data Setmentioning
confidence: 69%
“…4. Chickenpox The UCI Hungarian Chickenpox Cases dataset [40,16] consists of records of chickenpox cases weekly in 20 counties in Hungary. This dataset represents a realistic situation where generative models be trained on small amounts of data and then generate synthetic samples to train other models.…”
Section: Energymentioning
confidence: 99%
“…The chickenpox dataset [11] includes weekly chickenpox cases from 20 cities in Hungary. We performed predictions for Budapest.…”
Section: Alp-local For Predicting Chickenpox Casesmentioning
confidence: 99%